PROJECT-RESEARCH ACTIVITIES OF STUDENTS IN THE STUDY OF PHYSICS - Irmatov Fozil Muminovich (American Journals Publishing, 2024)
The article argues that, given the complex and abstract nature of physics, providing students with opportunities for practical experience and collaborative problem-solving is crucial for improving the effectiveness of physics education. Furthermore, the authors provide recommendations for integrating project-based learning within modern educational methodologies to increase the engagement and success of students in the study of physics.
Keywords: Project-based learning, research activities, physics education, independent learning, scientific thinking, problem-solving skills, experimental methods, collaborative learning, critical thinking, hands-on projects, physics curriculum, educational methodologies, student engagement, teamwork, practical experience, concept mastery.